Hydrostatic pressure and shear stress affect endothelin‐1 and nitric oxide release by endothelial cells in bioreactors. Issue 1 (17th September 2013) - Vozzi, Federico; Bianchi, Francesca; Ahluwalia, Arti; Domenici, Claudio
Abstract Abundant experimental evidence demonstrates that endothelial cells are sensitive to flow; however, the effect of fluid pressure or pressure gradients that are used to drive viscous flow is not well understood. There are two principal physical forces exerted on the blood vessel wall by the passage of intra‐luminal blood: pressure and shear. To analyze the effects of pressure and shear independently, these two stresses were applied to cultured cells in two different types of bioreactors: a pressure‐controlled bioreactor and a laminar flow bioreactor, in which controlled levels of pressure or shear stress, respectively, can be generated. Using these bioreactor systems, endothelin‐1 (ET‐1) and nitric oxide (NO) release from human umbilical vein endothelial cells were measured under various shear stress and pressure conditions. Compared to the controls, a decrease of ET‐1 production by the cells cultured in both bioreactors was observed, whereas NO synthesis was up‐regulated in cells under shear stress, but was not modulated by hydrostatic pressure. These results show that the two hemodynamic forces acting on blood vessels affect endothelial cell function in different ways, and that both should be considered when planning in vitro experiments in the presence of flow. Understanding the individual and synergic effects of the two forces could provide important insights into physiological and pathological processes involved in vascular remodeling and adaptation.